Nanostructured micro-raspberries from superparamagnetic iron oxide nanoparticles: Studying agglomeration degree and redispersibility of nanoparticulate powders via magnetisation measurements - Stauch, Claudia; Spaeth, Stephan; Ballweg, Thomas; Luxenhofer, Robert; Mandel, Karl (Journal of Colloid and Interface Science, 2017)
Surface modified superparamagnetic iron oxide nanoparticles are assembled into nanostructured micro-raspberry particles via spray drying. The micro-raspberry powder is readily redispersed to individual nanoparticles or nanostructured sub-units, depending on the initially adjusted nanoparticle modification. In this work, it is demonstrated how the technique of magnetic zero-field-cooled/field-cooled (ZFC/FC) measurements can be used to judge the degree of agglomeration, i.e. the extent of hard-agglomerates and soft-agglomerates in a system and predict the redispersibility of the powder particles. Furthermore, the uniformity of surface modification of the individual nanoparticles can be judged via this method. In addition, the technique can be applied to characterise complex nanostructured particle systems composed of iron oxide nanoparticles mixed with another type of nanoparticulate building-block. Thus, this work shows that magnetic measurement techniques are a promising approach to characterise agglomeration states of nanoparticles, their degree of surface modification and their distribution in complex particle and composite systems.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Field cooled/zero field cooled measurements; Magnetic nanoparticles; Nanostructured iron oxide particles; Raspberry-like particles; Redispersible nanoparticles